Granulometria do calcário e luz artificial para poedeiras comerciais no segundo ciclo de postura - Oliveira, Alexsandro Nunes de (2012)
The experiment was conducted to evaluate the effects of particle size of limestone and the use of artificial light for laying hens in the second laying cycle. It was used 240 Hisex White laying hens with 82 weeks of age in a completely randomized design in a 5 x 2 factorial arrangement, resulting in 10 treatments with 4 replicates of 6 birds. The variables were the five particle sizes obtained by increasing the proportion of thick limestone (0, 25, 50, 75 and 100%) compared thin limestone and two types of lighting, with and without artificial light. The particle size of limestone and the light did not affect the performance and egg quality. However, there were changes in the schedule of the birds feeding throughout the day in response to the lighting program. With respect to bone quality, it was observed that the density and mineral content of the tibia were not affected by the treatments, however, there was a quadratic effect of particle size of limestone on the deformity and bone strength, obtaining maximum inclusion points with 63% 59% of thick limestone, respectively. It is concluded that, although the lighting program may modify the behavior of intake throughout the day, the use of artificial light and the particle size of limestone does not influence the performance and egg quality of laying hens in the second production cycle, created at latitude 3°43’02” South and 38°32’35” west longitude. However, the use of limestone with higher granulate size is justified to maintain bone quality of these birds.